Evaluation of Epstein-Barr Virus Latent Membrane Protein 2 Specific T-Cell Receptors Driven by T-Cell Specific Promoters Using Lentiviral Vector - Dongchang Yang; Qing Shao; Hua Sun; Xiaoxin Mu; Yun Gao; Runqiu Jiang; Jiajie Hou; Kun Yao; Yun Chen; Beicheng Sun (Clinical and Developmental Immunology)
Transduction of latent membrane protein 2 (LMP2)-specific T-cell receptors into activated T lymphocytes may provide a universal, MHC-restricted mean to treat EBV-associated tumors in adoptive immunotherapy. We compared TCR-specific promoters of distinct origin in lentiviral vectors, that is, Vβ6.7, delta, luria, and Vβ5.1 to evaluate TCR gene expression in human primary peripheral blood monocytes and T cell line HSB2. Vectors containing Vβ 6.7 promoter were found to be optimal for expression in PBMCs, and they maintained expression of the transduced TCRs for up to 7 weeks. These cells had the potential to recognize subdominant EBV latency antigens as measured by cytotoxicity and IFN-γ secretion. The nude mice also exhibited significant resistance to the HLA-A2 and LMP2-positive CNE tumor cell challenge after being infused with lentiviral transduced CTLs. In conclusion, LMP2-specific CTLs by lentiviral transduction have the potential use for treatment of EBV-related tumors.